The slope intercept form of the equation y - 2 = 3(x + 1) is
y = 3x + 5.
According to the given question.
We have an equation
y - 2 = 3(x + 1)
As we know that the standard equation of line in slope intercept form is
y = mx + c.
Therefore,
The slope intercept form of the above equation y - 2 = 3(x + 1) is given by
y - 2 = 3(x + 1)
y - 2 = 3x + 3
⇒ y = 3x + 3 + 2
⇒ y = 3x + 5
Hence, the slope intercept form of the equation y - 2 = 3(x + 1) is
y = 3x + 5.
Find out more information about slope intercept form here:
https://brainly.com/question/9384144
#SPJ4